An empirical study of visitors’ motivations and actual behavior in dark tourism sites using structural equation modeling: Bangladesh perspective - Hossain, Md Shakhawat; Chowdhury, Md Sohel; Masud, Abdullah Al; Refat, Nazmul Hasan; Wu, Renhong (Journal of Tourism Management Research, 2024)
This study applies the Theory of Planned Behavior (TPB) to explore visitors’ motivations and their actual behavior at dark tourism sites (DTS) in Bangladesh. It integrates four key motivational dimensions—national identity, educational-historical exploration, empathy, and recognition—to assess how these motivations influence visitors’ attitudes (AT), behavioral intention (BI), and actual behaviors (AB). A total of 402 valid questionnaires were collected and examined using confirmatory factor analysis to assess the fit of the measurement model. This research utilized structural equation modeling (SEM) to assess the seven hypotheses. Empirical results show that visitors’ motivation has a positive impact on their attitude (AT) and behavioral intention (BI). Subjective norms (SN) and perceived behavioral control (PBC) are linked to the visitors’ intentions, and BI is linked to their AB. But AT to AB and AT to BI were not statistically significant. The study collected the information during the COVID-19 pandemic, without controlling for its potential effects, using a self-reported questionnaire from a single source. The research contributes to the current knowledge by examining visitors’ motivations and exploring their intentions and actual behavior toward DTS in the tourism field.